INFLASI, GROSS DOMESCTIC PRODUCT (GDP), CAPITAL ADEQUACY RATIO (CAR), DAN FINANCE TO DEPOSIT RATIO (FDR) TERHADAP NON PERFORMING FINANCING (NPF) PADA BANK UMUM SYARIAH DI INDONESIA - AKBAR, DINNUL ALFIAN (Islamic Economics Program, Faculty of Islamic Economics and Business, 2016)
When bank distributes its finance, the bank will always face credit risk. Credit risks arise if the bank could not get back from the principal of the loan installment that it provided. In this case, the level of problem loans can be demonstrated by the ratio of Non Performing Financing (NPF) in Islamic banks. The lower the NPF ratio, the better the condition of the bank, because the level of problematic financing is low.This study aimed to find out how the effect of inflation, Gross Domestic Product (GDP), Capital Adequacy Ratio (CAR), and Finance to Deposit Ratio (FDR) against Non Performing Financing (NPF) on Islamic Banks in Indonesia in the study period, from 2010 until 2014. the population used in this study were 12 Islamic banks registered in Indonesian banks by taking five samples of Islamic banks. The sampling method is using purposive sampling method. To explain the influence of these variables, the data obtained in this study were analyzed by using multiple linear regression model.The results of research by t test showed that the variables Gross Domesctic Product (GDP), Capital Adequacy Ratio (CAR), and Finance to Deposit Ratio (FDR) effect on Non Performing Financing (NPF), while variable which does not affect the Non Performing Financing (NPF) is inflation. Four variables influence simultaneously against Non Performing Financing (NPF).Kata kunci: Inflasi, Gross Domestic Product (GDP), Capital Adequacy Ratio (CAR), Finance to Deposit Ratio (FDR), dan Non Performing Financing (NPF)